3(x - 1)(x + 1) = 2(x - 2)(x + 2) + x^2 + 2x

aniavetisa aniavetisa    2   07.06.2020 11:16    0

Ответы
Slaeran Slaeran  15.10.2020 13:19

х = 2,5

Объяснение:

3(x - 1)(x + 1) = 2(x - 2)(x + 2) + x² + 2x

3(х²-1) = 2(х²-4) + х² + 2х

3х²-3 = 2х² - 8 + х² + 2х

3х² - 2х² - х² - 2х = - 8 + 3

-2х = -5

х = -5 : (-2)

х = 2,5

Формула сокращенного умножения :

Разность квадратов : (а-b)(a+b) = (а²- b²)

ПОКАЗАТЬ ОТВЕТЫ
Цири Цири  15.10.2020 13:19

3(x^2-1)=2(x^2-4)+x^2+2x

3x^2-3=2x^2-8+x^2+2x

3x^2-3=3x^2-8+2x

-3=-8+2x

2x=-5

x=-5/2

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра